An In-depth Analysis of the Contemporary Biological Characteristics of Aedes Mosquitoes in Laboratory Conditions - Abu Bakar, Azlinda; Zainudin, Muhammad Nur Hilmi (Journal of Sustainable Natural Resources, 2024)
Aedes aegypti and Aedes albopictus are recognized vectors of various arboviruses, including dengue, Zika, and chikungunya, contributing significantly to global public health challenges. The investigation aimed to clarify essential aspects of the biological dynamics of both Aedes species under standardized laboratory conditions. This included developmental duration, adult lifespan, gonotrophic cycle, and morphometric parameters across various life stages. Findings revealed that the lifecycle completion of Ae. aegypti and Ae. albopictus in laboratory settings averaged approximately 8.75 days and 10.35 days, respectively, with no statistically significant difference observed between the two species. Intriguingly, a notable difference in longevity was observed between male and female mosquitoes, with females showing significantly longer lifespans (P